A cell‐based high‐throughput protocol to screen entry inhibitors of highly pathogenic viruses with Traditional Chinese Medicines. Issue 5 (14th October 2016) - Yang, Yong; Cheng, Han; Yan, Hui; Wang, Peng‐Zhan; Rong, Rong; Zhang, Ying‐Ying; Zhang, Cheng‐Bo; Du, Rui‐kun; Rong, Li‐Jun
Abstract : Emerging viruses such as Ebola virus (EBOV), Lassa virus (LASV), and avian influenza virus H5N1 (AIV) are global health concerns. Since there is very limited options (either vaccine or specific therapy) approved for humans against these viruses, there is an urgent need to develop prophylactic and therapeutic treatments. Previously we reported a high‐throughput screening (HTS) protocol to identify entry inhibitors for three highly pathogenic viruses (EBOV, LASV, and AIV) using a human immunodeficiency virus–based pseudotyping platform which allows us to perform the screening in a BSL‐2 facility. In this report, we have adopted this screening protocol to evaluate traditional Chinese Medicines (TCMs) in an effort to discover entry inhibitors against these viruses. Here we show that extracts of the following Chinese medicinal herbs exhibit potent anti‐Ebola viral activities: Gardenia jasminoides Ellis, Citrus aurantium L., Viola yedoensis Makino, Prunella vulgaris L., Coix lacryma‐jobi L. var. mayuen (Roman.) Stapf, Pinellia ternata (Thunb.) Breit., and Morus alba L. This study represents a proof‐of‐principle investigation supporting the suitability of this assay for rapid screening TCMs and identifying putative entry inhibitors for these viruses. J. Med. Virol. 89:908–916, 2017 . © 2016 Wiley Periodicals, Inc.